Nitrile Substituents at the Conjugated Dipyridophenazine Moiety as Infrared Redox Markers in Electrochemically Reduced Heteroleptic Ru(II) Polypyridyl Complexes - Sumner, Elizabeth; Pižl, Martin; McQuaid, Kane T; Hartl, František (Inorganic chemistry, 2024)
Ruthenium(II) complexes [Ru(tap) (NN)] (tap = 1,4,5,8-tetraazaphenanthrene, NN = 11-cyano-dipyrido[3,2- :2',3'- ]phenazine (11-CN-dppz) and 11,12-dicyano-dipyrido[3,2- :2',3'- ]phenazine (11,12-CN-dppz)) feature the C≡N groups as infrared (IR)-active redox markers. They were studied by cyclic voltammetry, UV-vis, and IR spectroelectrochemistry (SEC), and density functional theory calculations to assign the four 1e reduction waves R1-R4 observed in dichloromethane. Generally, the NN ligands are reduced first (R1). For [Ru(tap) (11,12-CN-dppz)] , R1 is sufficiently separated from R2 and delocalized over both tap ligands. Accordingly, IR SEC conducted at R1 shows a large red shift of the ν (C≡N) modes by -18/-28 cm , accompanied by a 4-fold enhancement of the ν (C≡N) intensity, comparably with reference data for free 11,12-CN-dppz. The first tap-based reduction of spin-doublet [Ru(tap) (11,12-CN-dppz)] to spin-triplet [Ru(tap) (11,12-CN-dppz)] at R2 decreased ν(C≡N) by merely -2 cm , while the intensity enhancement reached an overall factor of 8. Comparably, a red shift of ν(C≡N) by -27 cm resulted from the 1e reduction of [Ru(tap) (11-CN-dppz)] at R1 (poorly resolved from R2), and the intensity enhancement was roughly 3-fold. Concomitant 1e reductions of the tap ligands (R2 and R3) caused only minor ν(C≡N) shifts of -3 cm and increased the absorbance by overall factors of 6.5 and 8, respectively.